Qualidade de vida de crianças e adolescentes com epilepsia no município de Maringá - Martins, Maria do Rosário [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Epilepsy is the most common chronic disorders in childhood. Traditionally, medical treatment was concerned with the control of seizures attempting to provide the medication with minimal adverse effects. In recent years studies have shown that the impact of clinical condition and medications extends far beyond the physical domain, potentially causing damage in a cognitive and social and behavioral level. Therefore an assessment of quality of life of children patients and their caregivers was added to clinical practice with the goal of improving the welfare of patients and family. Hence, this study aimed to evaluate the quality of life of children and adolescents with epilepsy attended by public healthcare system in Maringá and identify possible risk and protection factors. Specifically this study focused on the child's clinical and sociodemographic variables, coping strategies and caregiver burden. Fifty two dyads (child/caregiver) attending Neurology clinic and who met the inclusion criteria were selected. Participants responded to the following instruments: Quality of life evaluation scale (AUQEI), Quality of Life of Children with Epilepsy (QVCE 50), Impact of Childhood Illness Scale (ICIS), Ways of Coping Scale (EMEP) and the Zarit Burden Inventory (ZBI).After correcting the tests a descriptive statistical analysis was performed. In a second stage the data received inferential statistical analysis, including analysis of prediction. Participants age range was 4 to 12, 80.8% attended regular school and about half were male, with 0-4 years of education. The most recurrent type of illness condition was generalized epilepsy, while 57.7% of subjects had seizures that started before 4 years of age and 36.5% had daily seizures. ere taking carbamazepine for its control. The main caregiver was mostly the mother, with age range from 31 to 40 years, possessed companion, had 8 years or more of education, acted as caregivers for 8 years or more and ...

A epilepsia é um dos transtornos crônicos mais comuns na infância. Tradicionalmente, o tratamento médico preocupou-se com o controle das crises e que a medicação tivesse o mínimo de efeitos adversos. Em anos recentes, estudos mostram que o impacto do quadro clinico e das medicações estende-se muito além do domínio físico, podendo acarretar prejuízos a nível social, cognitivo e comportamental. Agregou-se a pratica clínica, a avaliação da qualidade de vida das crianças e de seus cuidadores, com o objetivo de melhorar o bem estar dos pacientes e da família. O presente estudo teve por objetivo avaliar a qualidade de vida de crianças e adolescentes com epilepsia na percepção do cuidador e da criança e identificar possíveis fatores de risco e proteção. Foram selecionadas 52 díades, criança/cuidador, que frequentavam o Ambulatório de Neurologia e preenchiam os critérios de inclusão. Os participantes responderam aos seguintes instrumentos: Questionário de Avaliação de Qualidade de Vida em Crianças e Adolescentes (AUQEI), Qualidade de Vida da Criança Epiléptica (QVCE 50), Escala de Impacto das Doenças na Infância (ICIS), Escala de Modos de Enfrentamento (EMEP) e o Inventário de Sobrecarga de Zarit (ZBI). Após a correção dos testes foi realizada analise estatística descritiva e, num segundo momento, os dados receberam tratamento estatístico inferencial, incluindo analise de predição. Os participantes tinham idade que variava de 4 a 12 anos, 80,8% frequentavam a escola regular e aproximadamente a metade era do sexo masculino, com 0 a 4 anos de estudo. O quadro mais recorrente foi de epilepsia generalizada; 57,7% dos sujeitos tinham crises que se iniciaram antes dos 4 anos de idade e 36,5% tinham crises diárias. A grande maioria das crises durava de 0 a 10 minutos e a maioria dos sujeitos fazia uso de carbamazepina para seu controle. O cuidador principal era, majoritariamente, a mãe, com idade entre 31 a ...
Quality of live of children and adolescents whith epilepsy in city of Maringá
Keywords: Crianças - Doenças; Adolescentes - Doenças; Neurologia pediatrica; Qualidade de vida; Maringa (PR); Pediatric neurology